Analysis Semiotics Of The Abadi Nan Jaya Film Poster Based On Charles Sanders Peirce's Theory - Nurul Mashlihah; Nurhijjah Nelly Waty Siregar; Nurlatifah; Tias Hadaning; Sarah; Mayang Pipit (International Journal of Technology and Education Research, 2026)
A film poster is a visual communication medium that not only functions as a promotional tool, but also as a sign system capable of constructing meaning, shaping perceptions, and directing audience expectations towards the film's content. This study aims to analyze the meaning contained in the Abadi Nan Jaya film poster using Charles Sanders Peirce's semiotic theory which includes representation, objects, interpretants, and the classification of signs in the form of icons, indexes, and symbols. This study uses a qualitative descriptive approach with a semiotic analysis method. The primary data is the official Abadi Nan Jaya film poster which is analyzed based on visual elements such as color, typography, character expressions, image composition, and cultural background. The results show that the poster is effective in constructing a representation of the post-plague world through the dominance of dark colors, zombie visuals, and the characters' expressions of fear. In addition to presenting a horror film image, the poster also contains a deeper meaning about the misuse of traditional knowledge, human ambition for immortality, and the collapse of the social order due to the exploitation of culture and scientific knowledge. The use of a village background and traditional herbs strengthens the local Indonesian identity, thus distinguishing this film from zombie films in general. Thus, the Abadi Nan Jaya poster not only functions as a promotional medium, but also as a cultural communication medium that conveys social criticism through a visual sign system. The findings of this study are expected to enrich semiotic studies in the field of visual communication and Indonesian film.